2010
DOI: 10.1021/ef100031s
|View full text |Cite
|
Sign up to set email alerts
|

NO Emission Characteristics of Low-Rank Pulverized Bituminous Coal in the Primary Combustion Zone of a Drop-Tube Furnace

Abstract: Experiments were conducted in a drop-tube furnace (DTF) to investigate NO emission characteristics of low-rank bituminous coal burning in the primary combustion zone. The combustion tests were performed under high-stoichiometric-ratio (SR) combustion conditions (SR g 1) and low-SR combustion conditions (SR<1). Along the length of the furnace, concentrations of flue gas species, such as NO, HCN, NH 3 , CH 4 , CO, CO 2 , and O 2 , were carefully measured during pyrolysis and different SR combustion conditions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…As the bituminous coal mixing ratio increases by 10%, the NO x emission concentration reduces by 15–20 mg/m 3 on average. The low‐NO x combustion technology of the coal‐fired boiler reduces the generation of NO x in the combustion process by controlling the conversion of the volatile nitrogen to nitrogen oxides 41 . Increasing the bituminous coal mixing ratio will increase the volatile content of the blended coals in the furnace.…”
Section: Resultsmentioning
confidence: 99%
“…As the bituminous coal mixing ratio increases by 10%, the NO x emission concentration reduces by 15–20 mg/m 3 on average. The low‐NO x combustion technology of the coal‐fired boiler reduces the generation of NO x in the combustion process by controlling the conversion of the volatile nitrogen to nitrogen oxides 41 . Increasing the bituminous coal mixing ratio will increase the volatile content of the blended coals in the furnace.…”
Section: Resultsmentioning
confidence: 99%
“…They attributed the increase of NO x in the FL zone to the oxidation of char-N. The results obtained by Fei et al 6 also showed that NO and its precursors can be effectively converted to N 2 in the FR zone under the staging condition, and they speculated that char-N is the main source of NO x in the FL zone. Fan et al 1 also found that burnout air injection would result in a further increase in NO x concentration.…”
Section: Introductionmentioning
confidence: 94%
“…In air-staging combustion, the FR zone is the major area for NO x reduction due to the reducing atmosphere. Therefore, the effect of key factors on NO x formation in the FR zone has attracted much interest from scholars. , Bai et al reported that NO x could be remarkably decreased in the FR zone when the elevated temperature and strong reducing atmosphere condition was available in this zone. This phenomenon was attributed to the fact that the reduction reaction of NO x was strengthened by elevated temperature under the strong reducing atmosphere.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations